Filipino Students’ Reading Abilities: A Note on the Challenges and Potential Areas for Improvement - Idulog, Mark Vergel; Gadiano, Ronald; Toledo, Edmon; Hermosada, Melanie; Casaldon, Hazel; Mariposa, Marianne; Geron, Christie; Dequito, Elena; Genanda, Jeromea; Malipot, Mark Anthony; Pentang, Jupeth Toriano; Bautista, Ronalyn (Yayasan Nurul Yakin Bunga Tanjung, 2023)
The reading abilities of Filipino students have been a challenge for educators and policymakers alike. Despite government efforts to improve literacy rates in the Philippines, recent studies have shown that many students need help with reading comprehension, vocabulary development, and critical thinking skills. This research note examines the current state of reading abilities among Filipino students and potential areas for improvement. The poor reading abilities can be attributed to several factors, including a lack of resources and socioeconomic factors. However, there are identified potential areas for improvement, such as promoting early literacy programs, investing in teacher training, and developing reading materials that are culturally relevant and engaging for Filipino students. These findings have important implications for education policies and practices in the Philippines and for educators and researchers seeking to improve reading abilities among Filipino students.